2008
DOI: 10.1002/jcp.21144
|View full text |Cite
|
Sign up to set email alerts
|

Reishi immuno‐modulation protein induces interleukin‐2 expression via protein kinase‐dependent signaling pathways within human T cells

Abstract: Ganoderma lucidum, a medicinal fungus is thought to possess and enhance a variety of human immune functions. An immuno-modulatory protein, Ling Zhi-8 (LZ-8) isolated from G. lucidum exhibited potent mitogenic effects upon human peripheral blood lymphocytes (PBL). However, LZ-8-mediated signal transduction in the regulation of interleukin-2 (IL-2) gene expression within human T cells is largely unknown. Here we cloned the LZ-8 gene of G. lucidum, and expressed the recombinant LZ-8 protein (rLZ-8) by means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Collectively, this polysaccharide-dependent expression of cytokines and Ig employed signaling through the activation of MAPKs and NF-κB [65]. In addition, an immunomodulatory protein, purified from G. lucidum, stimulated the production of IL-1β, IL-2, TNF-α and IFN-γ by human peripheral blood lymphocytes [66], and modulated protein tyrosine kinase (PTK) and protein kinase C (PKC) signaling to produce IL-2 in human T cells [67]. Interestingly, only one study describes an induction of the immune response by G. lucidum triterpene, ganoderic acid Me, as demonstrated by the increased expression of IL-2 and IFN-γ in mice [68].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this polysaccharide-dependent expression of cytokines and Ig employed signaling through the activation of MAPKs and NF-κB [65]. In addition, an immunomodulatory protein, purified from G. lucidum, stimulated the production of IL-1β, IL-2, TNF-α and IFN-γ by human peripheral blood lymphocytes [66], and modulated protein tyrosine kinase (PTK) and protein kinase C (PKC) signaling to produce IL-2 in human T cells [67]. Interestingly, only one study describes an induction of the immune response by G. lucidum triterpene, ganoderic acid Me, as demonstrated by the increased expression of IL-2 and IFN-γ in mice [68].…”
Section: Discussionmentioning
confidence: 99%
“…The LZ-8 expression plasmid and the purification of rLZ-8 protein were performed as previously described [34].…”
Section: Preparation Of the Recombinant Ling Zhi-8 (Rlz-8 Or Lz-8) Prmentioning
confidence: 99%
“…23 In addition, LZ-8 can work as a mitogen to activate T cells. 24 Jeurink et al reported that protein extracts of G. lucidum contain immunomodulating activity by acting directly on monocytes, 25 implying that proteins including LZ-8 in G. lucidum may stimulate myeloid cells. However, many other immunoregulatory functions of LZ-8 remain to be explored.…”
Section: Dna Vaccines For Cancer Therapymentioning
confidence: 98%